2022
DOI: 10.1001/jamanetworkopen.2022.47632
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chlorhexidine Use and Scaling and Root Planing With Birth Outcomes in Pregnant Individuals With Periodontitis

Abstract: ImportanceChlorhexidine mouthwash enhances treatment effects of conventional periodontal treatment, but data on chlorhexidine as a source of heterogeneity in meta-analyses assessing the treatment of maternal periodontitis in association with birth outcomes are lacking.ObjectiveTo assess possible heterogeneity by chlorhexidine use in randomized clinical trials (RCTs) evaluating the effect of periodontal treatment (ie, scaling and root planing [SRP]) vs no treatment on birth outcomes.Data SourcesCochrane Oral He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The SRs analyzed in this study spanned from 2003 to 2023 and were conducted in various countries, including Saudi Arabia [ 43 ], the United Kingdom [ 21 , 44 ], the United States [ 45 , 46 , 47 , 48 , 49 ], Vietnam [ 50 ], Canada [ 51 , 52 ], Australia [ 53 , 54 ], India [ 55 , 56 ], Brazil [ 10 , 57 , 58 , 59 , 60 ], Germany [ 61 ], Italy [ 62 ], and Greece [ 63 , 64 ]. Additional details regarding the characteristics of these SRs can be found in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SRs analyzed in this study spanned from 2003 to 2023 and were conducted in various countries, including Saudi Arabia [ 43 ], the United Kingdom [ 21 , 44 ], the United States [ 45 , 46 , 47 , 48 , 49 ], Vietnam [ 50 ], Canada [ 51 , 52 ], Australia [ 53 , 54 ], India [ 55 , 56 ], Brazil [ 10 , 57 , 58 , 59 , 60 ], Germany [ 61 ], Italy [ 62 ], and Greece [ 63 , 64 ]. Additional details regarding the characteristics of these SRs can be found in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven SRs [ 10 , 21 , 44 , 45 , 46 , 50 , 59 ] were considered to have high confidence, fourteen SRs [ 43 , 47 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 61 , 62 , 63 , 64 ] had low confidence, and three SRs [ 48 , 49 , 60 ] had critically low confidence ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Polish study [37] stated that the use of zinc ions, commonly found in commercial anti-malodor mouthwashes, can inhibit F. nucleatum. A Columbian systematic review and meta-analysis conducted by Merchant et al [95] indicated that treating maternal periodontitis patients infected with F. nucleatum using chlorhexidine mouthwash, scaling and root planing (SRP) reduces the risk of preterm birth and low birth weight babies. These reports highlight the importance of considering multiple external factors that impact a pregnant woman's oral microbiota and potentially lead to APOs.…”
Section: Gestational Diabetesmentioning
confidence: 99%
“…In recent years, some systematic reviews of quantitative analyses on pregnancy and periodontal disease are available, which focus on specific subfields such as the prevalence of periodontal disease in pregnancy, 13 oral microflora, 13 associations of periodontal disease with different adverse outcomes, [14][15][16] or specific interventions to improve prognosis. [17][18][19] However, there is still a paucity of macroscopic analyses of the knowledge profile and topic evolution in the field.…”
Section: Introductionmentioning
confidence: 99%